Alienation: The Perpetual Trauma: The Impact of Political Independence and Apartheid on African Writers (Journal of Advances and Scholarly Researches in Allied Education, 2017)
It has been a destiny that the African writers were devoid to express themselves freely with their spontaneous gust of feeling and devoid from literature. These writers have delved deep into the several reasons for alienation. In this arena Eskia Mphahlele, a freedom fighter for Africans posits a vantage point as how this concept of exile affects the individual as a whole even after the political independence and how they remain secluded in their home.To project the real cause of alienation in Africa was the sole intention of Eskia Mphahlele. In this juncture the election of Nationalist caused a sense of release for this alienation in South Africa. Hence to understand South Africa it is necessary to know black writers. Apartheid led people into racial discrimination and segregation. The Population Registration Act (1950) provided a framework to portray racial category of every person, the Immortality Act (1950), made marriage and sexual relation between races illegal, the separate Amenities Act (1953), proved authenticity to segregation in public places, Bantu homelands legislation provided for the creation of black African reserves and authorized the government to grant homeland’s independence.